2009
DOI: 10.1111/j.1365-2141.2009.07870.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospho‐STAT5 and phospho‐Akt expression in chronic myeloproliferative neoplasms

Abstract: Summary The majority of Myeloproliferative Neoplasms (MPNs) are characterised by mutations in genes encoding molecules or receptors involved in cell signalling, the most common being the JAK2 V617F mutation. This mutation leads to ligand‐independent activation of downstream signalling pathways by constitutive phosphorylation. The signalling pathways affected include the Janus kinase‐signal transducers and activators of transcription (JAK‐STAT) and phosphotidylinositide‐3 kinase (PI3K) pathways, which regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 46 publications
2
48
1
Order By: Relevance
“…11 Increased phosphorylation of STAT5 and Akt was demonstrated by immunocytochemistry in the BM of patients with MPN. 12 Finally, RAD001 prevented in vitro cytokine-stimulated and cytokine-independent growth of primary MPN patients' cells, 14 overall providing a rationale for exploring the effectiveness of mTOR targeting in MPN treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Increased phosphorylation of STAT5 and Akt was demonstrated by immunocytochemistry in the BM of patients with MPN. 12 Finally, RAD001 prevented in vitro cytokine-stimulated and cytokine-independent growth of primary MPN patients' cells, 14 overall providing a rationale for exploring the effectiveness of mTOR targeting in MPN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] A prominent feature of the pathogenesis of MF, as well as of MPN in general, is the direct or indirect activation of the JAK/STAT pathway by mutated proteins, 9 providing the rationale for the use of JAK2 inhibitors. 10 However, dysregulated activation of the PI3K/Akt and ERK downstream pathways in MPN cells has also been described, [11][12][13] and we recently reported that RAD001, a specific inhibitor of mammalian target of rapamycin (mTOR) signaling, prevented proliferation of MPN cell lines and primary cells 14 (C. Bogani, manuscript submitted, June 2011).…”
Section: Introductionmentioning
confidence: 99%
“…V617F is associated with significantly increased levels of phospho-Akt in hematopoietic cells, 103,104 and multiple groups have shown synergism between JAK2 inhibitors and agents that interrupt the phosphatidylinositol-3-kinase/Akt/mammalian target of rapamycin (PI3K/Akt/mTOR) axis in MPNs, both in vitro and in vivo. 105,106 Promising results were obtained with single-agent everolimus in patients with MF, particularly with regard to relief of MPN-associated symptoms.…”
Section: Jak2mentioning
confidence: 99%
“…1 --6 Based on findings of pre-clinical studies, we performed a phase I clinical study of WT1 peptide immunotherapy for patients with AML, myelodysplastic syndromes, breast or lung cancer, and were able to confirm the safety and clinical efficacy of this therapy. 7 In this report, we describe the long-term outcome for AML patients enrolled in this study.…”
mentioning
confidence: 99%
“…4 Although small molecule Jak2 inhibitors are entering clinical trials, their ultimate efficacy is unclear. 5 In addition to the concern of insufficient inhibition of mutated Jak2 in vivo or the emergence of resistance through activation of complementary pathways, many MPNs contain other mutational events (for example, mutation in exon12 of Mpl, 6 or the KIT D618V mutation in patients with systemic mastocytosis 7 ), and thus are not sensitive to Jak inhibitors. Therefore, the development of inhibitors to common mediators of diverse signaling pathways in this disease is very desirable.…”
mentioning
confidence: 99%